A SIMPLE SPECTROPHOTOMETRIC METHOD FOR THE QUANTITATIVE ANALYSIS OF PHOSPHATE IN THE WATER SAMPLES - Habibah, Nur; Dhyanaputri, I Gusti Ayu Shri; Karta, I Wayan; Sundari, Cokorda Dewi Widhya Hana; Hadi, Mochammad Choirul (JST (Jurnal Sains dan Teknologi), 2018)
A simple spectrophotometric method was used to determine the phosphate content in the water sampels. The method is based on the formation of molybdenum blue complex from the reaction of orthophosphate and ammonium molybdate followed by reduction with ascorbic acid in the aqueous sulfuric acid medium. The color intensity of the molybdenum blue complex is proportionally to the phosphate content in the solution. The system obeys Lamber-Beer’s Law at the 890 nm in the concentration range of 0.1-1 mg P/L and the linier calibration graph was obtained with the slope, 0.6334, intercept, 0.0074 and correlation coefficient of 0.9988. This official method was also used for the quantitative analysis of phosphate in the water samples and the satisfactory result was obtained. The range of phosphate concentration in the water samples are 0.033 – 2.943 mg P/L.